1984
DOI: 10.1002/1097-4679(198405)40:3<743::aid-jclp2270400318>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining fantasies and self-concept among college students

Abstract: Examined the relationship among 10 different types of sustaining fantasies, which make individuals feel better during stressful and/or disappointing times, and two measures of poor self‐concept, self‐derogation and instability of self‐concept. One hundred twenty‐four college student Ss, 48 males and 76 females, responded to the Sustaining Fantasy Questionnaire of Zelin et al., Kaplan's Self‐Derogation Scale, and Rosenberg's Instability of Self Scale. Canonical correlation, bivariate correlations, and correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…They are the repetitive fantasies, easily retrieved into consciousness, that an individual uses to create a situation that is either more ideal or counter to the situation that is causing the stress. These fantasies are viewed as necessary for adaptive coping because they enable the individual to restore self-esteem and emotional equilibrium in the face of stress (Harder & Zelin, 1984;Zelin et al, 1983). An example of a sustaining fantasy is the adolescent, rejected for a date by a girl, who finds himself imagining striking out the side in an important baseball game (Zelin et al, 1983).…”
Section: Studymentioning
confidence: 99%
“…They are the repetitive fantasies, easily retrieved into consciousness, that an individual uses to create a situation that is either more ideal or counter to the situation that is causing the stress. These fantasies are viewed as necessary for adaptive coping because they enable the individual to restore self-esteem and emotional equilibrium in the face of stress (Harder & Zelin, 1984;Zelin et al, 1983). An example of a sustaining fantasy is the adolescent, rejected for a date by a girl, who finds himself imagining striking out the side in an important baseball game (Zelin et al, 1983).…”
Section: Studymentioning
confidence: 99%
“…Previous studies (Greenwald & Harder, 1994;Harder, Zelin, et al, 1984;Zelin et al, 1983) have found that Power and Revenge, Death and Illness, Suffering, and Withdrawal and Protection are all associated with measures of psychopathology. The IPI scales' correlation with psychopathology appears to be quite consistent, then, with the SFQ findings and also with a previous normative study (Singer & Antrobus, 1972) that linked IPI responses to measures of maladjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mental imagery may be one of the common sustaining strategies employed by people to handle distressing events. Sustaining fantasies may create an alternative "reality" (e.g., experiencing one's own attractiveness, being in a powerful position) that may counter the original stressprovoking event, reduce related distress, and restore selfesteem (e.g., Harder et al, 1984;Zelin et al, 1983). These fantasies are typically consistent with both self-reported daydreams (i.e., fantasies experienced during less stressful circumstances) and behavioral coping style (e.g., Greenwald & Harder, 1995.…”
Section: The Present Researchmentioning
confidence: 99%